Discovering the Intriguing Dynamics of Transfer Pricing: Tax Burden, Foreign Ownership, and Company Size - Nelfin Nofrianti Lase; Yunia Oktari (Komunitas Dosen Indonesia, 2024)
ownership, and company size on transfer pricing practices within the mining subsector of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. Through purposive sampling, 35 datasets out of a total population of 40 companies were selected for analysis. Multiple linear regression served as the analytical tool, and hypothesis testing was executed using SPSS version 25 software. The findings underscore that both tax burden and foreign ownership wield significant influence over transfer pricing practices. Notably, companies exhibit a propensity to leverage transfer pricing as a strategic tool for tax burden management, particularly in instances of heightened foreign ownership. Interestingly, however, company size does not exhibit a significant impact on transfer pricing practices, suggesting that entities of varying magnitudes within this subsector tend to adopt analogous approaches to transfer pricing policies. These findings are pivotal for both regulatory bodies and corporate managers, as they provide valuable insights into the factors shaping transfer pricing practices. Moreover, the formulation of tax policies geared towards fostering transparency and equity in business operations. By comprehensively understanding the dynamics at play in transfer pricing, stakeholders can navigate regulatory landscapes more adeptly and devise strategies that promote fairness and compliance within the realm of taxation. This study thus contributes to the broader discourse on tax policy and corporate governance, offering a nuanced understanding of the intricate relationship between tax structures, ownership dynamics, and corporate practices within the mining subsector of Indonesia's manufacturing industry.